Tissue optics light scattering methods and instruments for medical diagnosis - Tuchin, V. V. (SPIE/International Society for Optical Engineering, 2007)
This second edition covers the intensive growth in tissue optics--in particular, the field of tissue diagnostics and imaging--that has occurred since 2000. As in the original edition, Part I describes fundamentals and basic research, and Part II presents instrumentation and medical applications. The extensive new material includes results on tissue optical property measurements, including polarized light interaction with turbid tissues; an overview of new polarization imaging and spectroscopy techniques, optical computed tomography (OCT) developments and applications; updates on controlling tissue optical properties, and the optothermal and optoacoustic interaction of light with tissues; and descriptions of fluorescence, nonlinear spectroscopies, and inelastic light scattering.
Keywords: Tissues -- Optical properties.; Light -- Scattering.; Diagnostic imaging.; Imaging systems in medicine.; elektronické knihy; electronic books